MATERNAL HYPOTHYROIDISM AND ITS EFFECTS ON NEONATAL THYROID FUNCTION: A RETROSPECTIVE STUDY - VIJAYALAKSHMI CHANDRASEKHAR; KOMAL SAHITHI BARLA; SUCHITRA PUSAPATI; VISWA KALYAN KOLLI; VENKATA MANASA RONGALA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to correlate maternal factors (age, parity, type of delivery, thyroid-stimulating hormone [TSH], and thyroxine [T4] values) and the newborn factors (gestational age, birth weight, and gender) with the TSH and T4 values of the newborn. Methods: A retrospective observational study was conducted on 90 hypothyroid mothers who were delivered at our Institute between January 2022 and March 2023. The 90 neonates born to these hypothyroid mothers underwent newborn screening tests for thyroid functions (tri-iodothyronine, T4, TSH) after 72 h of birth. These values were statistically analyzed with respect to maternal and fetal parameters. Results: 7 of the 90 neonates (7.77%) had elevated TSH values, i.e., >10 mIU/L. T4 values were abnormal in 31 neonates (34.4%), i.e., <11 ug/dL or >21.5 ug/dL but had normal TSH values. There was only one case where T4 levels were low and TSH level elevated. The correlation of TSH values with maternal and fetal parameters such as age of mother, parity, gestational age, baby weight, type of delivery, and the gender of the baby was not significant as p-values were all >0.05. There is a weak negative correlation (r=−0.044) between maternal TSH and neonatal TSH values which was statistically not significant. However, the maternal TSH and baby weight values are having positive correlation (r=0.113). Conclusion: Our study showed no significant correlation between maternal hypothyroidism and newborn TSH and T4 values which may be due to early antennal recognition and supplementation with levothyroxine.